Evaluating Affective User-Centered Design of Video Games Using Qualitative Methods - Yiing Y’ng Ng; Chee Weng Khong; Robert Jeyakumar Nathan (International Journal of Computer Games Technology)
In recent years, researchers and practitioners in the human-computer interaction (HCI) community have placed a lot of focus in developing methods and processes for use in the gaming field. Affective user-centered design (AUCD) plays an important role in the game industry because it promotes emotional and mental communication, hence improving the interaction modes between users and video games. This paper looks at the development of a suitable AUCD guideline to determine if the expressed emotion, semantics, and mental concept of a tangible and intangible video gaming interface are well received by its intended users. Approaching AUCD in video games requires investigating multiple data to obtain a reliable data especially when assessing and interpreting affect and emotion. They present a challenge due to many ambiguities related to affect definition and measuring affective emotion can be very tedious due to its complexity and unpredictability. In this paper, we describe the methods and techniques used to assess affective user-centered design in video games. We also discuss our approaches within the context of existing affective gaming and user-centered design theory and data gathering procedures, including the factors affecting internal and external validity and the data analysis techniques.